If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 + 4x + -8 = 13 Reorder the terms: -3 + -8 + 2x + 4x = 13 Combine like terms: -3 + -8 = -11 -11 + 2x + 4x = 13 Combine like terms: 2x + 4x = 6x -11 + 6x = 13 Solving -11 + 6x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 6x = 13 + 11 Combine like terms: -11 + 11 = 0 0 + 6x = 13 + 11 6x = 13 + 11 Combine like terms: 13 + 11 = 24 6x = 24 Divide each side by '6'. x = 4 Simplifying x = 4
| 5*29= | | 7x-8y=64 | | 11*15= | | 2(x-4)(x-3)=x-13 | | 9x+6=9(x-3) | | X+4/3=x-8/5 | | X/4-3=-4 | | -8-3+6*2= | | 3z=14-29 | | 3(3m-2)+10=3(m-4)-3 | | 23x-7-14x+4=25x-4-16x+12 | | (5a-2)(7a+3)=0 | | 0.14(y-6)+0.04y=0.08y-0.1 | | 5-5(-5-7/-6)-13 | | -4(4x+1)=-52 | | 6x^2=10x+4 | | 3a-6x+4-12a+3x= | | 3(x+2)=-2(x-8) | | x(1-x)=25(x-1) | | 4-(-2n+3)=44 | | x+x+7=160 | | 12x-5=6x-31 | | x(x+9)=-2(x+9) | | 0.9*x+7.8*y=114 | | -3b+4/3b=-40/9 | | 2a+a+6-13= | | 2a+a+6-13 | | -3y-15=7y+25 | | x+8forx=5 | | 3-2(n-9)=9 | | 2y+6x=8 | | -4=n-2+3 |